(untitled) (Global Journal of Science Frontier Research, 2012)
Recently the synthesis of [3-13 C]-, [4-13 C]-, and [11-13 C]-porphobilinogen, [ 15 N, 13 C4]-1H - pyrrole-2,3,5 -tricar -boxylic acid, [1-15 N]-3-cyano-4-methyl-1H-pyrrole and [2-13 C]-and [3-13 C]-cyano-4methyl-3-pyrrolin-2-one have been published. Incorporation of 13 C and 15 N in these systems at any position and combination of positions has become accessible. Also mild alkylations of active methylene compounds with α-halo carbonyl compounds open up many 3-pyrrolin-2-ones and pyrrole systems based on stable isotope building blocks that have been published. This gives the access to a whole new library of stable isotope enriched pyrroles in any stable isotope enriched form. This is also the case for biliverdin IXα which after enzymatic treatment has been converted into (2R)-phytochromobilin that reacts with its apoprotein to form intact active phytochrome.